Increased Productivity towards the Success of Nothopanax Scutellarium in Case Of Hepatoprotector and Nefroprotector - Sri Wahyuni Nasution (Budapest International Research and Critics University, 2021)
This study aims to determine the concentration of bowl leaf extract (Nothopanax scutellarium) which is effective in protecting impaired liver and kidney function. Liver damage can cause metabolic disorders in the body, which will lead to homeostatic disorders. Acute renal failure is a clinical problem, occurring frequently and characterized by a relatively sudden decline in renal function. This research is qualitative experimental research using a male rat (Rattus norvegicus) which is healthy and has normal activity, with a bodyweight of 200 g. Male rats were adapted to be kept in cages for 7 days. Adaptation needed to be done to avoid the risk of stress in mice which could affect blood serum content. During the adaptation period, male rats are only given standard food and have not been given any treatment. At the end of the adaptation period, serum analysis was carried out in the five treatment groups. The results of the data obtained from this study were analyzed using the Oneway-Anova test.